Performance of Distress Thermometer: A Study among Cancer Patients - Thapa, Sudip; Sharma, Susmita; Gautam, Nishim; Shrestha , Sudip; Raj Ghimire , Bijesh; Dahal, Sanuja; Adhikari, Bibhav; Maharjan, Rubina; Thapa, Sadiksha; Kattel, Regina; Koirala, Rishav (Journal of Nepal Health Research Council, 2024)
Background: The Distress Thermometer accompanied with Problems List is a commonly used screening tool for psychosocial distress. However, it’s cut-off score, performance and risk factors for psychosocial distress varies among studies. This is the first study conducted in Nepal to investigate the Distress Thermometer’s screening properties, its optimal cut-off score and evaluating the prevalence of psychosocial distress and its risk factors.Methods: This cross-sectional study enrolled 162 heterogeneous cancer patients. The English form of the Distress Thermometer was translated to Nepali using a forward and backward translation method. Questionnaires including socio-demographic, clinical characteristics, the Hospital Anxiety and Depression Scale and Distress Thermometer accompanied with Problems List were filled. Receiver Operating Characteristic analysis of distress thermometer scores was evaluated against Hospital Anxiety and Depression Scale-Total (?15). An Area Under the Curve, sensitivity, specificity, positive predictive value and negative predictive value were calculated at each Distress Thermometer cut-off score. Results: Receiver Operating Characteristic analysis showed an excellent discriminating performance (Area Under the Curve =87.4%). A cut-off score of 4 on Distress Thermometer was established and it yielded sensitivity (88.9%), specificity (71.1%), positive predictive value (75.4%) and negative predictive value (86.5%) respectively. Furthermore, 55.6% of participants were distressed and emotional problems (odd ratio = 28.00), practical problems (odd ratio = 12.152) and physical problems (odd ratio = 2.397) were found to be significant risk factors for PD.Conclusions: PD is a global burden in cancer patients. The DT with a cut-off score of 4 accompanied with PL is valid instrument for screening PD in Nepali cancer patients. PL identified the problems that causes of PD.Keywords: Cancer; Distress Thermometer; Nepal.